Men and Masculinities in Irish Cinema, by Debbie Ging - Barry Monahan (Alphaville: Journal of Film and Screen Media, 2013)
As its title suggests, Debbie Ging’s Men and Masculinities in Irish Cinema sets out to consider a broad historical track of films produced in or about Ireland, by engaging with them through a gender-focussed theoretical lens. Ging promises from the outset, and delivers across ten roughly chronologically unfolding chapters, a close analytical reading of the construction of masculinity from the earliest incarnations of the Irish male on screen to more contemporary representations. In doing so, Ging shows sensitivity to the various sociopolitical and historical contexts within—or against—which each of the gendered characterisations has emerged in over a century of cinema, of which, arguably, only approximately three decades could be offered as Irish film by Irish filmmakers.